2015
DOI: 10.1039/c4mb00406j
|View full text |Cite
|
Sign up to set email alerts
|

Systems biosynthesis of secondary metabolic pathways within the oral human microbiome member Streptococcus mutans

Abstract: Streptococcus mutans, a Gram-positive human commensal and pathogen, is commonly recognized as a primary causative agent in dental caries. Metabolic activity of this strain results in the creation of acids and secreted products are recognized as pathogenic factors and agents that promote immunomodulation by stimulating the release of pro-inflammatory cytokines. Products of secondary metabolic pathways of microorganisms from the human microbiome are increasingly investigated for their immunomodulatory functions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…mutans , trans-2-decenoic acid, which suppressed morphogenesis at concentrations that do not affect fungal growth. Zvanych et al [ 30 ] tested whether mutanobactins display any immunomodulatory activity using in vitro models of macrophage cell line. Interestingly, mutanobactin B caused a significant increase in pro-inflammatory cytokines, such as IL-6 and Il-12, suggesting that mutanobactins may play an important role in modulating immune response.…”
Section: Discussionmentioning
confidence: 99%
“…mutans , trans-2-decenoic acid, which suppressed morphogenesis at concentrations that do not affect fungal growth. Zvanych et al [ 30 ] tested whether mutanobactins display any immunomodulatory activity using in vitro models of macrophage cell line. Interestingly, mutanobactin B caused a significant increase in pro-inflammatory cytokines, such as IL-6 and Il-12, suggesting that mutanobactins may play an important role in modulating immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Many small molecules of bacterial origin are produced by organized genes groups called biosynthetic gene clusters (BGCs). Common types of BGCs harbored by the oral microbiota include polyketide (PKS), nonribosomal peptide synthases (NRPS), hybrid PKS/NRPS, and ribosomally synthesized and posttranslationally modified peptides (RiPPs) that are represented by bacteriocins (i.e., mutacins) as well as other small molecules with various activities, such as biofilm formation, bacterial cell signaling, stress response, and host colonization (Wu et al 2010; Merritt and Qi 2012; Zvanych et al 2015; Liu et al 2016; Aleti et al 2019). Recent studies have identified novel PKS/NRPS hybrids responsible for the production of mutanicyclin and 3 structural variants of reutericyclin (Hao et al 2019; Tang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…1a ). Six other structures, the mutanolins ( 12–17 ), a consequence of cysteine incorporation in the final module of the NRPS assembly line, were also found (Zvanych et al, 2015 ) (Fig. 1a ).…”
Section: Mutanobactinsmentioning
confidence: 76%
“…Zvanych et al identified and proposed partial structures for a litany of mutanobactin-like molecules through MS/MS fragmentation and isotope labeling studies. First, Zvanych et al found several other mutanobactin congeners, B2 ( 4 ) and E–J ( 6–11 ) (Zvanych et al, 2015 ) (Fig. 1a ).…”
Section: Mutanobactinsmentioning
confidence: 98%